An integrated approach to assess the impacts of zinc pyrithione at different levels of biological organization in marine mussels. (April 2018) - Dallas, Lorna J.; Turner, Andrew; Bean, Tim P.; Lyons, Brett P.; Jha, Awadhesh N.
Abstract: The mechanisms of sublethal toxicity of the antifouling biocide, zinc pyrithione (ZnPT), have not been well-studied. This investigation demonstrates that 14-d sublethal exposure to ZnPT (0.2 or 2 μM, alongside inorganic Zn and sea water controls) is genotoxic to mussel haemocytes but suggests that this is not caused by oxidative DNA damage as no significant induction of oxidised purines was detected by Fpg-modified comet assay. More ecologically relevant endpoints, including decreased clearance rate (CR), cessation of attachment and decreased tolerance of stress on stress (SoS), also showed significant response to ZnPT exposure. Our integrated approach was underpinned by molecular analyses (qRT-PCR of stress-related genes, 2D gel electrophoresis of proteins) that indicated ZnPT causes a decrease in phosphoenolpyruvate carboxykinase (PEPCK) expression in mussel digestive glands, and that metallothionein genes are upregulated; PEPCK downregulation suggests that altered energy metabolism may also be related to the effects of ZnPT. Significant relationships were found between % tail DNA (comet assay) and all higher level responses (CR, attachment, SoS) in addition to PEPCK expression. Principal component analyses suggested that expression of selected genes described more variability within groups whereas % tail DNA reflected different ZnPT concentrations. Highlights: We describe an integrated approach to determine the impacts of ZnPT on marine mussels. Results suggest that ZnPT is able to induce DNA damage in marine invertebrates. Low concentrations of ZnPT cause tissue-specific upregulation of stress-related genes. ZnPT-specific effects on protein profiles were observed in the digestive gland. Relationships between DNA damage and higher level effects were significant.